Major Depressive Disorder (MDD) and Antidepressant Medication Are Overrepresented in High-Dose Statin Treatment - Leutner, Michael; Matzhold, Caspar; Kautzky, Alexander; Kaleta, Michaela; Thurner, Stefan; Klimek, Peter; Kautzky-Willer, Alexandra (Frontiers in Medicine, 2021)
Objective: To examine the dose-dependent relationship of different types of statins with the occurrence of major depressive disorder (MDD) and prescription of antidepressant medication. Methods: This cross-sectional study used medical claims data for the general Austrian population (n=7,481,168) to identify all statin-treated patients. We analyzed all patients with MDD undergoing statin treatment and calculated the average defined daily dose for six different types of statins. In a sub-analysis conducted independently of inpatient care, we investigated all patients on antidepressant medication (statin-treated patients: n=98,913; non-statin-treated patients: n=789,683). Multiple logistic regression analyses were conducted to calculate the risk of diagnosed MDD and prescription of antidepressant medication in patients treated with different types of statins and dosages compared to non-statin-treated patients. Results: In this study, there was an overrepresentation of MDD in statin-treated patients when compared to non-statin-treated patients (OR:1.22,95%CI:1.20-1.25). However, there was a dose dependent relationship between statins and diagnosis of MDD. Compared to controls, the ORs of MDD were lower for low-dose statin-treated patients (simvastatin>0–<=10mg:OR:0.59,95%CI:0.54-0.64; atorvastatin>0–<=10mg:OR:0.65,95%CI:0.59-0.70; rosuvastatin>0–<=10 mg:OR:0.68,95%CI:0.53–0.85). In higher statin dosages there was an overrepresentation of MDD (simvastatin>40–<=60mg:OR:2.42,95%CI:2.18–2.70, >60–80mg:OR:5.27,95%CI:4.21–6.60; atorvastatin>40–<=60mg:OR:2.71,95%CI:1.98-3.72,>60–<=80mg:OR:3.73,95%CI:2.22–6.28; rosuvastatin>20–<=40mg:OR:2.09,95%CI:1.31-3.34). The results were confirmed in a sex-specific analysis and in a cohort of patients taking antidepressants, prescribed independently of inpatient care. Conclusions: This study shows that it is important to carefully re-investigate the relationship between statins and MDD. High-dose statin treatment was related to an overrepresentation, low-dose statin treatment to an underrepresentation of MDD.